Lifting index of the niosh lifting equation and low back pain - Remor Teixeira, Eliana (2011)
The purpose of this study is to assess the relationship of the Lifting Index obtained through the application of the NIOSH Lifting Equation and the incidence of low back pain among forty-eight workers involved in manual lifting tasks. It was applied the equation in eleven tasks and the workers were interviewed. The most unfavorable conditions presented themselves in the lifting destination. The variables that most contributed to the inadequate values of the Lifting Index were: the horizontal location, the lifting frequency and the vertical distance, beyond the high weight of the load. The incidence of low back pain in the last twelve months was 19%, whereas the incidence of work-related low back pain in the same period was 10%. In 72.7% of the tasks evaluated the Composite Lifting Index was more than three, which are considered as high ergonomic risk.